Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd002106.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Dressings for superficial and partial thickness burns

Abstract: Issue 3. Cochrane Reviews are regularly updated as new evidence emerges and in response to comments and criticisms, and the Cochrane Database of Systematic Reviews should be consulted for the most recent version of the Review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
119
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(122 citation statements)
references
References 8 publications
0
119
0
3
Order By: Relevance
“…19 Nevertheless, there has been an increase in the development of silver-containing dressings for the management of both chronic and acute wounds. 20 The use of topical negative pressure therapy for wound care has become widespread since 1997, when published work demonstrated that VAC assisted in completion of wound closure and enhanced formation of granulation tissue in the wound bed. 21 The development of negative pressure wound therapy has continued to expand to optimize patient care, and in 2008 a silver-impregnated sponge used in conjunction with the VAC device (V.A.C.…”
Section: Discussionmentioning
confidence: 99%
“…19 Nevertheless, there has been an increase in the development of silver-containing dressings for the management of both chronic and acute wounds. 20 The use of topical negative pressure therapy for wound care has become widespread since 1997, when published work demonstrated that VAC assisted in completion of wound closure and enhanced formation of granulation tissue in the wound bed. 21 The development of negative pressure wound therapy has continued to expand to optimize patient care, and in 2008 a silver-impregnated sponge used in conjunction with the VAC device (V.A.C.…”
Section: Discussionmentioning
confidence: 99%
“…In the first study, honey is evaluated for wound healing [1], and in the other, different dressings are studied for their healing properties [2]. Doctors and consumers are increasingly demanding more separation between marketing campaign to sustain products, superstition, myth remedies and evidence.…”
Section: The Methodsologist's Point Of Viewmentioning
confidence: 99%
“…Another Cochrane review analysed a total of 26 randomised controlled trials that evaluated whether any type of dressing from the many now commercially available is more effective in promoting healing and minimising discomfort and infection for patients with superficial and partial thickness burns [2]. A number of dressings appear to have some benefits over other products in burn management, and this benefit relates to time to wound healing, the number of dressing changes and the level of pain experienced.…”
Section: Best Among the Commercial Dressingsmentioning
confidence: 99%
“…Durante los últimos años, se han publicado avances importantes aplicables a una nueva GPC, destacando revisiones sistemáticas y meta análi-sis sobre la calidad metodológica de los estudios randomizados realizados en pacientes quemados 25 , manejo tópico de las quemaduras [26][27][28][29] , nutrición 30,31 y rehabilitación 32 ; además de GPC acerca de manejo de catástrofes 33,34 , manejo prehospitalario 35 , resucitación 36 , manejo de quemaduras intermedias 37 , criterios diagnósticos de sepsis 38 , uso de terapia antibiótica 39 , nutrición 40,41 , ventilación mecánica en pacientes quemados 42,43 y diagnóstico y manejo de neumonía asociada a ventilador mecánico 44 . Esperamos que nuestro trabajo sea tomado como un aporte al mejoramiento continuo de las GPC más que una crítica a las mismas.…”
Section: Importancia De Recomendaciones Mbeunclassified